Religious and sustainability: Studi integrasi antara pentakostalisme, populisme, dan politik - Sitorus, Pontus; Pasaribu, Jonias (Sekolah Tinggi Teologi Pelita Bangsa, Jakarta, 2024)
As part of the world community, Pentecostals must consider their role in achieving the Sustainable Development Goals (SDGs). This role must be carried out in various aspects, including socio-political with a populism approach to unify the identity of Pentecostalism. This research integrates Pentecostalism, politics, and populism to achieve sustainable development. The research method used is descriptive qualitative with a constructive theological approach. The research results show that Pentecostalism populism in politics has a cheerful face in efforts to achieve sustainability. The universalism of the Sustainable Development Goals (SDGs) must be combined with a more internal view and involve the Pentecostal community in the struggle for hegemony over the concept of sustainable development. Populism, which often mobilizes support through emotional issues and religious identity, can be integrated with sustainability strategies through religious communities providing spiritual and moral support. Integration between Pentecostalism, populism, and politics to achieve effective and inclusive sustainable development while recognizing the challenges and need for adaptation in the face of global social, political, and economic change.Â AbstrakPentakostal sebagai bagian dalam masyarakat dunia ditantang untuk memikirkan peranannya dalam mencapai tujuan Sustainable Development Goals (SDGs). Peranan tersebut mesti dilakukan dalam berbagai aspek, termasuk sosial-politik dengan pendekatan populisme sebagai sarana pemersatu identitas Pentakostalisme. Tujuan penelitian ini adalah mengintegrasikan antara Pentakostalisme, politik, dan populis sebagai sarana untuk mencapai pembangunan berkelanjutan. Metode penelitian yang digunakan adalah kualitatif deskriptif dengan pendekatan teologi konstruktif. Hasil penelitian menunjukkan bahwa populisme Pentakostalisme dalam politik berwajah positif dalam upaya mencapai sustainability. Tujuan Pembangunan Berkelanjutan PBB harus dipadukan dengan pandangan yang lebih internal dan melibatkan komunitas Pentakostal dalam perjuangan mendukung dan menolak hegemoni atas konsep pembangunan berkelanjutan. Populisme, yang seringkali memobilisasi dukungan melalui isu-isu emosional dan identitas religius, dapat diintegrasikan dengan strategi keberlanjutan melalui komunitas agama yang menyediakan dukungan spiritual dan moral. Integrasi antara Pentakostalisme, populisme, dan politik sebagai sarana untuk mencapai pembangunan berkelanjutan yang efektif dan inklusif, sambil mengakui tantangan dan kebutuhan adaptasi dalam menghadapi perubahan sosial, politik, dan ekonomi global.